E-cigarette Marketing Exposure and Subsequent Experimentation Among Youth and Young Adults - Chen-Sankey, Julia Cen (Pediatrics, 2019)
OBJECTIVES: Electronic cigarette (e-cigarette) use has become increasingly prevalent among US youth and young adults in recent years. Exposure to e-cigarette marketing may stimulate e-cigarette use. In this study, we estimated the longitudinal association between e-cigarette marketing exposure and e-cigarette experimentation among US youth and young adult never tobacco users. METHODS: The analysis included nationally representative samples of youth (ages 12–17; n = 8121) and young adult (ages 18–24; n = 1683) never tobacco users from wave 2 (2014–2015) and wave 3 (2015–2016) of the Population Assessment of Tobacco and Health Study. In the study, researchers measured past-month exposure to e-cigarette marketing through various places (eg, Web sites and events) at wave 2 and e-cigarette experimentation at wave 3. Statistical analysis included multivariable regressions to examine the associations between wave 2 e-cigarette marketing exposure and wave 3 e-cigarette experimentation. RESULTS: At wave 2, 70.7% of youth and 73.9% of young adult never tobacco users reported past-month exposure to e-cigarette marketing; at wave 3, 4.9% and 4.5% of youth and young adults experimented with e-cigarettes, respectively. Youth and young adults exposed to e-cigarette marketing at wave 2 were more likely (adjusted odds ratio = 1.53, 95% confidence interval = 1.07–2.17; and adjusted odds ratio = 2.73, 95% confidence interval = 1.16–6.42, respectively) to have experimented with e-cigarettes at wave 3 than those not exposed. Marketing exposure through each place at wave 2 was associated with e-cigarette experimentation at wave 3. CONCLUSIONS: E-cigarette marketing exposure predicted subsequent e-cigarette experimentation among youth and young adult never tobacco users. Increased restrictions on marketing through various channels may help minimize their exposure to e-cigarette marketing messages.